Pripovedovalec in fokalizacija - Zupan Sosič, Alojzija (Primerjalna književnost, 2014)
The narrator and focalization are mediators/conveyors and drivers of a narrative. The former tells the story (using his voice) and the latter focalizes the narrative information (through the eyes) - the narrative system distinguishes between the subject of speech (the narrator) and the subject of perspective (the focalizer). In her overview of narrator types, the author takes into account the (grammatical) person or various participants in the story (first-person, second-person, or third-person narrator), the mode in which the narrative information is conveyed (auctorial/omniscient narrator vs. figural narrative situation), the reliability of the information conveyed (reliable or unreliable narrator), and classification by typical speech act or type of narration (reporter, explainer, or evaluator).
Keywords: naratologija; narratology; pripovedna tehnika; nezanesljivi pripovedovalec; implicitni avtor; pripovedna perspektiva; fokalizacija